2019
DOI: 10.1038/s41598-019-40137-0
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Event Detection in Temporal Networks

Abstract: We propose a method for detecting large events based on the structure of temporal communication networks. Our method is motivated by findings that viral information spreading has distinct diffusion patterns with respect to community structure. Namely, we hypothesize that global events trigger viral information cascades that easily cross community boundaries and can thus be detected by monitoring intra- and inter-community communications. By comparing the amount of communication within and across communities, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
(18 reference statements)
0
30
0
Order By: Relevance
“…Moriano and co-authors state in their paper [64] that "Global events trigger viral information cascades that easily cross community boundaries and can thus be detected by monitoring intra-and inter-community communications." ey showed, when a global event (Boston Marathon bombing) occurs, it spreads virally, crossing community boundaries and producing more intercommunity.…”
Section: Resultsmentioning
confidence: 99%
“…Moriano and co-authors state in their paper [64] that "Global events trigger viral information cascades that easily cross community boundaries and can thus be detected by monitoring intra-and inter-community communications." ey showed, when a global event (Boston Marathon bombing) occurs, it spreads virally, crossing community boundaries and producing more intercommunity.…”
Section: Resultsmentioning
confidence: 99%
“…The suggested method used for event detection is motivated by the fact that viral information spreading has distinct diffusion/spread patterns with respect to the community structures. Specifically, Moriano et al [152] suggest that global events trigger viral information cascades and can thus be detected by monitoring intra-and inter-community communications that occur across the community boundaries. By comparing the expanse of communication patterns among intra-and inter-communities, authors show that it is possible to detect several types of events, even when they do not trigger a significantly larger communication among users.…”
Section: Community-based Event Detection In Temporal Network Via Gramentioning
confidence: 99%
“…By comparing the expanse of communication patterns among intra-and inter-communities, authors show that it is possible to detect several types of events, even when they do not trigger a significantly larger communication among users. A schematic representation of the proposed event detection method taken from the Moriano et al [152] study is shown in Figure 43. From Figure 43, it can be observed that for each network, nodes are belonging to the same communities but different patterns of communication within and across communities appear.…”
Section: Community-based Event Detection In Temporal Network Via Gramentioning
confidence: 99%
“…• Analysis of the political representativeness of Twitter users [3] • Real-time Twitter analysis [4][5][6] • Democratic elections [7][8][9][10][11][12][13] • The uses of Twitter by populists [14] • Misinformation dissemination and event detection in social networks [15][16][17] • Online public shaming [18] • and many more Furthermore, there exist plenty of public available datasets. E.g., a curated collection [19] is hosted on Zenodo [20] and covers several datasets of political campaigns [8,9], online misinformation networks [21], event detection in temporal networks [22], public shaming [23], Twitter-related word vectors [24], retweeting timeseries [25], and even continuously updated samples of a nations-wide Twitter usage [26].…”
Section: Introductionmentioning
confidence: 99%